2013
DOI: 10.1128/jvi.03061-12
|View full text |Cite
|
Sign up to set email alerts
|

Complex Alternative Cytoplasmic Protein Isoforms of the Kaposi's Sarcoma-Associated Herpesvirus Latency-Associated Nuclear Antigen 1 Generated through Noncanonical Translation Initiation

Abstract: bKaposi's sarcoma-associated herpesvirus (KSHV) latency associated-nuclear antigen 1 (LANA1) protein is constitutively expressed in all KSHV-infected cells, as well as in all forms of KSHV-associated malignancies. LANA1 is a multifunctional KSHV oncoprotein containing multiple repeat sequences that is important for viral episome maintenance and the regulation of cellular and viral gene expression. We characterize here multiple LANA1 isoforms and show that ϳ50% of LANA1 is naturally generated as N-terminally tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 59 publications
4
43
0
Order By: Relevance
“…In contrast, the function of the recently discovered cytoplasmic isoforms of LANA, generated by noncanonical translation initiation within the LANA NTD (35,56) or possibly by caspase cleavage (24), has not been explored to date. In this study, we report that LANA, especially its cytoplasmic isoforms, antagonizes the function of cGAS, hereby promoting lytic replication after lytic cycle induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the function of the recently discovered cytoplasmic isoforms of LANA, generated by noncanonical translation initiation within the LANA NTD (35,56) or possibly by caspase cleavage (24), has not been explored to date. In this study, we report that LANA, especially its cytoplasmic isoforms, antagonizes the function of cGAS, hereby promoting lytic replication after lytic cycle induction.…”
Section: Discussionmentioning
confidence: 99%
“…LANA is known to be a nuclear protein forming nuclear speckles in KSHV-infected cells. A recent study reported the existence of cytoplasmic isoforms of LANA, which are mainly generated by noncanonical internal translation initiation sites localized within the LANA N-terminal domain (35). Another recent report suggested the existence of N-terminally truncated LANA forms resulting from caspase cleavage (24).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the names of both proteins specify, and restrictively imply, a nuclear localization. Recently, we have shown that cytoplasmic forms of truncated LANA1 exist (16). In this report, our data demonstrate that the major EBV and KSHV oncogenes generate additional, highly divergent frameshifted protein products.…”
Section: Lana1 Generates −2 Alternative Reading Frame (Lana1 Arf ) Prmentioning
confidence: 59%
“…The shorter form of the doublet is due to an alternative C-terminal polyadenylation site (15). More recently, even faster migrating isoforms have been characterized to result from in-frame, internal translation initiation at sites in the N-terminal and CR1 regions (16). All of these known isoforms have the same amino acid sequence as canonical LANA1 and differ only in being N-or C-terminally truncated.…”
mentioning
confidence: 99%